Effects of Interval Training and a Taper on Cycling Performance and Isokinetic Leg Strength - Martin, D. T.; Scifres, J. C.; Zimmerman, S. D.; Wilkinson, J. G. (International Journal of Sports Medicine, 1994)
The purpose of this study was to determine whether changes in isokinetic leg strength parallel changes in cycling performance during a six-week high-intensity aerobic interval training program and a subsequent two-week taper. Eleven male collegiate cyclists participated in one competitive cycling graded exercise test, four consecutive days of aerobic intervals (30 min @ 82.2 + or - 0.74% HRmax, 1:1 work:releif), and four continuous rides (1-2 hr @ 65-80% HRmax) weekly. Pedaling cadence during training was generally 70-80 rpm suggesting a knee joint velocity of approximate 210 degrees sec- 1. Cycling performance and peak isokinetic torque (TQpk) for knee flexors (HAM) and knee extensors (QUAD) @ 30, 120, 210, and 300 degrees were assessed before, every two weeks during, and each week for two weeks following six weeks of interval training. Performance increased significantly during training (15%) and increased further during the taper (8%). QUAD TQpk @ 30 and 120 degrees sec-1 and HAM TQpk for all velocities were not significantly elevated following training. Interestingly, QUAD TQpk @ 300 but not 210 degrees sec-1 significantly increased during the taper. Data from this study demonstrates that high-intensity aerobic interval cycling can promote gains in QUAD strength which occur primarily at contraction velocities slower than those utilized during cycling training. Additionally, a two-week taper can produce significant improvements in cycling performance (8%) and QUAD strength (8-9%) at 30 and 120 degrees sec-1, however, the time courses for these improvements do not parallel one another.